ANALISIS PROSEDUR PEMBERIAN KREDIT DAN PENAGIHAN PIUTANG DALAM MEMINIMALKAN PIUTANG TIDAK TERTAGIH PADA PT ANEKA TATA NIAGA - Sugianto, Julita; Natalia, Erni Yanti (SCIENTIA JOURNAL, 2021)
Every company needs to compete for the survival of its company. An action a company can take is to make sales on credit. However, sales on credit carry the risk of uncollectible accounts. The company must be able to properly review the implementation of sales, crediting and collection procedures. The purpose of this study is to analyze the procedures for granting credit and collection of accounts receivable in minimizing uncollectible accounts. The method used in this study is a qualitative research method with observative data collection, interviews, and documentation. The research population is PT Aneka Tata Niaga, and the research sample is uncollectible accounts receivable. The result of this research is that the procedure for granting credit begins with filling out a new customer form and then approved by the sales manager and director, accounts receivable collection is carried out by the accounts receivable admin section in preparing invoices and receipts needed in billing, bad debts are caused by internal and external factors, the obstacles encountered is to have a simple system of controlling accounts receivable based on manual in Microsoft Excel. The system that is planned to minimize uncollectible accounts is to form a system in GF Accounting.